Recent progress in cassava varietal improvement in India - Rajendran, P.G.; Nair, S.G.; Amma, C.S. Easwari; Vasudevan, Ke; Sreekumari, M.T. (International Center for Tropical Agriculture, 1995)
In India cassava breeding is done mainly at the Central Tuber Crops Research Institute (CTCRI) in Trivandrum, as well as in the State Agricultural Universities through the All India Co-ordinating Centres. CTCRI maintains 786 exotic and 848 indigenous accessions of cassava and 8 wild species in its germplasm bank. Coordinating Centres maintain about 280 indigenous accessions. Seedling progenies of 158 and 19 CIAT cassava accessions were screened at the Regional Centre of CTCRI in Bhubaneswar during 1985 and 1990, respectively. High root yields of more than 4 kg/plant were recorded in seedling progenies of CM3426, CM4046 and CM4229. Selection of promising germplasm and hybridization among selected accessions have been the principal strategies in cassava breeding. The most popular eating variety in Kerala, M-4, was introduced from Malaysia in the 1950s. Three high yielding hybrids, H-165, H-226 and H-97 were released in 1971 by CTCRI, of which H-165 and H-226 have become popular in Tamil Nadu for starch production. In 1983, 'Sree Sahya' and 'Sree Vishakam' were released at the national level. 'Sree Prakash' is a short duration cultivar released by CTCRI in 1987. In 1993 the Tamil Nadu Agricultural University released a high yielding, short-duration cultivar, called 'Co-3', which is reported to be tolerant to CMD. Recently, the Kerala Agricultural University also released a short-duration cultivar, called 'Nidhi', which can be harvested in 5 1 /2 - 6 months and has been recommended for paddy fallows of central Kerala. Two high yielding high quality short-duration cultivars, which can be harvested at six months, have been identified from the germplasm of CTCRI and are now being evaluated in advanced yield trials. A study on hybrid vigor in cassava indicated the predominance of non-additive gene action for root yield and yield components, indicating the possibility of exploiting hybrid vigor. Seven elite top-cross selections have been identified with high root yield, starch and dry matter contents and with low HCN content. By successive cycles of recurrent selection among germplasm accessions, the carotene content of roots could be raised significantly. Induction of triploidy has been found to be very effective for the development of high yielding, high starch and high dry matter cassava cultivars. A promising triploid, 2/14, is being considered for release for starch processing. Recently, successful induction of mutation has been reported in M-4. A few useful mutants, having higher root yields (20-25%) and high dry matter and starch contents, have been selected from single node cuttings of gamma-irradiated stakes. Studies on the use of true seed revealed the possibility of enhancing the multiplication rate more than 15 fold compared to the traditional method of vegetative propagation. A few promising seedling families have been identified, which give seedling yields comparable to clonal yields. Cassava mosaic disease is considerably reduced in seedling families.